2019
DOI: 10.1111/bioe.12670
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare organizations and high profile disagreements

Abstract: In this paper, we examine healthcare organizations’ responses to high profile cases of doctor–parent disagreement. We argue that, once a conflict crosses a certain threshold of public interest, the stakes of the disagreement change in important ways. They are no longer only the stakes of the child’s interests or who has decision‐making authority, but also the stakes of public trust in healthcare practitioners and organizations and the wide scale spread of medical misinformation. These higher stakes call for ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Moore and Lantos have analyzed high‐profile disagreements between families and hospitals and noted that many conflicts begin with an SM post that goes “viral,” sometimes unintentionally 29,30 . At least one parent in our study described feeling that her large SM following influenced her daughter's doctors’ willingness to try interventions identified through SM.…”
Section: Discussionmentioning
confidence: 84%
“…Moore and Lantos have analyzed high‐profile disagreements between families and hospitals and noted that many conflicts begin with an SM post that goes “viral,” sometimes unintentionally 29,30 . At least one parent in our study described feeling that her large SM following influenced her daughter's doctors’ willingness to try interventions identified through SM.…”
Section: Discussionmentioning
confidence: 84%
“…Whether they should seek to engage with international colleagues and advocate strongly for their own clinical position or develop consensus international professional referral standards. Moore and Lantos41 previously suggested that clinicians should use non-adversarial methods—by avoiding ‘fighting back’ with direct approaches, or ‘ducking for cover’ in the face of online scrutiny or critique. Rather, clinicians should share open, optimal information with families to enhance therapeutic alliances, and institutions should harness public relations platforms to promote best practice to the wider health community.…”
Section: Using Ethics Principles and Questions To Navigate The ‘Crowd...mentioning
confidence: 99%
“…Yet, a significant concern is that as a result of these high-profile cases and the public disagreements they involved, health professionals may develop reluctance in confronting the reality of futility, when continued intervention may support the wishes of parents. 9,10…”
Section: Introductionmentioning
confidence: 99%
“…Yet, a significant concern is that as a result of these high-profile cases and the public disagreements they involved, health professionals may develop reluctance in confronting the reality of futility, when continued intervention may support the wishes of parents. 9,10 In this paper, we seek to offer a pragmatic and accessible approach to understanding how futility is professionally, ethically and legally approached and understood when there are disagreements as to what is in the best interests of the child with a life-limiting condition. It is not our intention to address specific individual issues within the aforementioned cases, but rather explain that these cases have challenged paediatric intensive care practice and therefore that they highlight the importance of moral and ethical reasoning in contextualising futility as an integral part of this complex area of clinical care.…”
Section: Introductionmentioning
confidence: 99%